PENGARUH PENDIDIKAN KESEHATAN TENTANG PENCEGAHAN SERANGAN STROKE TERHADAP PENGETAHUAN WARGA RT 40 KELURAHAN PLAJU ILIR PALEMBANG - Setiawan; Shinta Maharani; Rahmalia Afriyani (LPPM STIKes Mitra Adiguna, 2022)
Abstract The aim of this research was to know is there any influence of health education on prevention of stroke toward the knowledge of Urban Village 40th’s residence at Plaju Ilir’s district of Palembang. The method of this research waspre experimental with one group pre-test and post-test, the total sample was 33 respondents through purposive sampling. This research was conducted at Urban Village 40th’s residence at Plaju Ilir’s district of Palembang and it was held in October 2021. Based on bivariate analysis, the result of statistic result was found that p-value=0.000<0.05, it concluded that there were a influence in giving health education on prevention of stroke toward knowledge of Urban Village 40th’s residence at Plaju Ilir’s district of Palembang. It concluded that by giving health education on prevention of stroke could influencetoward knowledge of Urban Village 40th’s residence at Plaju Ilir’s district of Palembang. Keywords:Health education, Prevention of stroke